Growth curves of fodder cereals. III.Rye (Secale cereale L.) (Semiárida, 2020)
The trial was carried out to study dry matter yields of 6 rye (Secale cereale L.) cultivars, and the seasonal growth distribution. Green standing crop was clipped every 7 days in 90 plots arranged at random in 5 series with 3 repetitions each, The growth equations of each cultivar was determined. The growing period was extended until last october. Significant differences (P < 0,05) in dry matter yields were observed; highest productions were for M. Suquía, O, Enrique and Tropero cultivara. Naicó and D. Luis cultivars showed a higher dry matter distribution than the rest during the winter season.
Keywords: rye; production; growth curves